Detecting Concealed Information from Groups Using a Dynamic Questioning Approach: Simultaneous Skin Conductance Measurement and Immediate Feedback - Meijer, Ewout H.; Bente, Gary; Ben-Shakhar, Gershon; Schumacher, Andreas (Frontiers in Psychology, 2013)
Lie detection procedures typically aim at determining the guilt or innocence of a single suspect. The Concealed Information Test (CIT), for example, has been shown to be highly successful in detecting the presence or absence of crime-related information in a suspect’s memory. Many of today’s security threats, however, do not come from individuals, but from organized groups such as criminal organizations or terrorist networks. In this study, we tested whether a plan of an upcoming mock terrorist attack could be extracted from a group of suspects using a dynamic questioning approach. One-hundred participants were tested in 20 groups of 5. Each group was asked to plan a mock terrorist attack based on a list of potential countries, cities and streets. Next, three questions referring to the country, city, and street were presented, each with 5 options. Skin conductance in all 5 members of the group was measured simultaneously during this presentation. The dynamic questioning approach entailed direct analysis of the data, and if the average skin conductance of the group to a certain option exceeded a threshold, this option was followed up. E.g., if the reaction to the option ‘Italy’ exceeded the threshold, this was followed up by presenting 5 cities in Italy. Results showed that in 19 of the 20 groups the country was correctly detected using this procedure. In 13 of these remaining 19 groups the city was correctly detected. In 7 of these 13, the street was also correctly detected. The question about the country resulted in no false positives (out of 20), the question about the city resulted in 2 false positives (out of 19), while the question about the streets resulted in 2 false positives (out of 13). Furthermore, the 2 false positives at the city level also yielded a false positive at the street level. Taken together these results indicate our dynamic questioning approach can help to unveil plans about a mock terrorist attack.